2002
DOI: 10.1124/dmd.30.6.676
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Sodium Nitrite-Induced Methemoglobinemia in the Rat

Abstract: ABSTRACT:A biologically based mathematical model was created to characterize time and dose-dependent relationships between exposure to nitrite and induction of methemoglobinemia. The model includes mass action equations for processes known to occur: oral absorption of nitrite, elimination from the plasma, partitioning between plasma and erythrocytes, binding of nitrite to hemoglobin and methemoglobin, and the free radical chain reaction for hemoglobin oxidation. The model also includes Michaelis-Menten kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 21 publications
3
63
0
1
Order By: Relevance
“…Previous pharmacokinetic studies of nitrite in the rat [24] predict a plasma concentration of 30 ÎŒM 15 minutes after intravenous administration at the optimal dose of 4 mg/kg. Thirty micromolar nitrite conferred cardioprotection in our in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous pharmacokinetic studies of nitrite in the rat [24] predict a plasma concentration of 30 ÎŒM 15 minutes after intravenous administration at the optimal dose of 4 mg/kg. Thirty micromolar nitrite conferred cardioprotection in our in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…Titov and Petrenko (2) could not induce considerable hemoglobin oxidation in erythrocyte lysate by submillimolar levels of nitrite without addition of high levels of H 2 O 2 . On the other hand, as a consequence of poisoning, the nitrite level in plasma may reach 100 -400 M resulting in severe methemoglobinemia (1,34). The gastrointestinal absorption of nitrite is quick and complete, following by a rapid NO 2 decay accompanied with fast development of the maximal metHb level in plasma (35).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of nitrite in blood can trigger the oxidation of hemoglobin, leading to methemoglobinemia (1,2). The mechanism of nitrite-dependent oxidation of deoxyhemoglobin (deoxyHb) 2 under anaerobic conditions, and its physiological potential in hypoxic vasodilation has recently been established (3)(4)(5).…”
mentioning
confidence: 99%
“…Nitrites are seldom found at detectable levels in tissues and bodily fluids following consumption and are unlikely to accumulate in tissues; it is hypothesised that this is due to the rapid oxidation of nitrite to nitrate and the rapid and extensive excretion of nitrite (Walker 1996;European Food Safety Authority 2009). The scientific literature on the pharmacokinetics (depletion rates) demonstrates that NaNO 2 is rapidly excreted, with plasma elimination half-life values under 1 hour for numerous species of mammals (Schneider & Yeary 1975;Kohn et al 2002). This characteristic, coupled with NaNO 2 being less toxic than most other vertebrate pesticides, could be viewed as being indicative of a low risk of secondary poisoning (Boink & Speijers 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant time × group interaction (F( 6,21 )=2.18, P = 0.153) and no significant difference between treatment groups (F( 2,7 )=1.78, P = 0.237). acute toxicity of NaNO 2 versus other vertebrate toxic agents and the rapid excretion of NaNO 2 (Kohn et al 2002;MRI 2004 . As well as no obvious signs of methaemoglobinaemia being observed in dogs, cats or chickens, the blood chemistry parameters analysed for dogs and cats indicated that after they consumed possum carcasses their liver and renal function remained normal and there was no damage to muscle tissue.…”
Section: Dogsmentioning
confidence: 99%